2002
DOI: 10.1021/bi025568u
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfers in the β-Reaction Catalyzed by Tryptophan Synthase

Abstract: Reactions catalyzed by the beta-subunits of the tryptophan synthase alpha(2)beta(2) complex involve multiple covalent transformations facilitated by proton transfers between the coenzyme, the reacting substrates, and acid-base catalytic groups of the enzyme. However, the UV/Vis absorbance spectra of covalent intermediates formed between the pyridoxal 5'-phosphate coenzyme (PLP) and the reacting substrate are remarkably pH-independent. Furthermore, the alpha-aminoacrylate Schiff base intermediate, E(A-A), forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Solution studies and x-ray structures have shown that the MVC-bound internal and external aldimine intermediates have the open conformation, while the α-aminoacrylate and quinonoid intermediates have the closed conformation (3, 5, 15, 16, 1822). The reaction of L-Ser with the MVC-bound and -free forms of α 2 β 2 results in the formation of equilibrating mixtures dominated by E(Aex 1 ), λ max = 424 nm, and E(A-A), λ max = 350 and 460 nm (9, 10, 11, 13, 14, 3133). Figure 2A compares the static spectra for the reaction of L-Ser in the presence or absence of Na + , Cs + , or NH 4 + .…”
Section: Resultsmentioning
confidence: 99%
“…Solution studies and x-ray structures have shown that the MVC-bound internal and external aldimine intermediates have the open conformation, while the α-aminoacrylate and quinonoid intermediates have the closed conformation (3, 5, 15, 16, 1822). The reaction of L-Ser with the MVC-bound and -free forms of α 2 β 2 results in the formation of equilibrating mixtures dominated by E(Aex 1 ), λ max = 424 nm, and E(A-A), λ max = 350 and 460 nm (9, 10, 11, 13, 14, 3133). Figure 2A compares the static spectra for the reaction of L-Ser in the presence or absence of Na + , Cs + , or NH 4 + .…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction data collected for these crystals were processed and scaled using HKL2000 (14). Both crystals belong to the space group P3 2 21. The details and statistics of the data collection are summarized in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…(v) The external aldimine accumulation is favored at high pH both in solution and in the crystalline state, whereas the ␣-aminoacrylate is stabilized at low pH (32)(33)(34). (vi) The conversion of the external aldimine to the aminoacrylate is accompanied by the release of a proton originating from the Schiff base nitrogen (24). Surprisingly, no studies have addressed the pH dependence of the catalytic rates on the S. typhimurium enzyme, the form for which the three-dimensional structure of the internal aldimine (12,15,35), the external aldimine (35,36), and the ␣-aminoacrylate (12) has been determined.…”
Section: Tryptophan Synthase Ph-dependent Catalysis 29573mentioning
confidence: 99%
“…This key catalytic intermediate predominantly absorbs at 350 -360 nm extending with broad bands at 470 nm. These bands have been attributed to either the enolimine and ketoenamine tau-tomers, respectively (23), or to an unprotonated and protonated aminoacrylate Schiff base, respectively (24). In tyrosine phenol-lyase and tryptophan indole-lyase, the predominant form of the ␣-aminoacrylate absorbs at 350 nm (25), whereas in Oacetylserine sulfhydrylase, the predominant form absorbs at 470 nm (26).…”
mentioning
confidence: 99%